Identification of Cattle Farms Chain Madura Ecosystem Based Blue Economy Concept - M. Fuad FM; Asfan; Millatul Ullya; Khoirul Hidayat (Nusantara Science and Technology Proceedings)
Madura Island is known as the island with agro climatic conditions are quite extreme. This condition affects the genius and plant populations that exist and the impact on animal life in these ecosystems. Ranch as one of the agricultural sector with a strategic position, as a provider of animal protein. Madura Island has an advantage in the field of cattle breeding typical Madura. The purpose of this study is assessing alternative commodity ecosystem chain efficiency improvements especially cattle cow Madura. The method used is descriptive method of analysis. The results showed a 7 supporting the plant ecosystem sustainability and development of cattle breeding Madura ie ecosystems rice, maize, soybeans, peanuts, green beans, cassava and sweet potatoes. Each ecosystem has the potential of different crops in each district to be integrated with the development of cattle breeding Madura.